2014
DOI: 10.2134/agronj14.0102
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Response of Maize Yield to Edaphic and Meteorological Conditions in a Saline Farmland

Abstract: Spatiotemporal variability of crop production strongly depends on soil heterogeneity, meteorological conditions, and their interaction. Canopy reflectance can be used to describe crop status and yield spatial variability. The objectives of this work were to understand the spatiotemporal variability of maize (Zea mays L.) yield using ground-based reflectance acquisitions in a salinity-and water-stress-affected 21-ha field beside the Venice Lagoon, Italy. Intra-and interannual reflectance variations were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…2007). Indeed, as also observed in other regions Scudiero et al, 2014), differences in reflectance between consecutive years were remarkable. Consequently, remote sensing data from a single (random) year should not be used when trying to map salinity, as the risk of producing poor results is clear.…”
Section: Multi-year Landsat 7 Reflectance Vs Soil Salinitysupporting
confidence: 82%
See 4 more Smart Citations
“…2007). Indeed, as also observed in other regions Scudiero et al, 2014), differences in reflectance between consecutive years were remarkable. Consequently, remote sensing data from a single (random) year should not be used when trying to map salinity, as the risk of producing poor results is clear.…”
Section: Multi-year Landsat 7 Reflectance Vs Soil Salinitysupporting
confidence: 82%
“…4) should therefore be considered fairly high. For comparison, Scudiero et al (2014) studied the 3-year temporal variability of corn reflectance in an area characterized by contrasting soils and affected by multiple stress types, including salinity and water stress. They observed that NDVI temporal variability could be used to identify (qualitatively) saline areas, but could only account for a small amount of its variations (R 2 = 0.11) due to the biasing effects of other abiotic stresses constantly occurring over time.…”
Section: Multi-year Landsat 7 Reflectance Vs Soil Salinitymentioning
confidence: 99%
See 3 more Smart Citations